2015
DOI: 10.1055/s-0034-1391375
|View full text |Cite
|
Sign up to set email alerts
|

Non-neoplastic pathology results after endoscopic submucosal dissection for gastric epithelial dysplasia or early gastric cancer

Abstract: Complete lesion removal by biopsy, pathology overestimation, and incorrect localization of the original tumor with subsequent ESD at the wrong site were the main reasons for non-neoplastic results after ESD. Small tumor size and surface area, and low sampling ratios were associated with non-neoplastic pathology results after ESD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…Therefore, ER could be regarded as an improved diagnostic procedure for early gastric neoplasms [5]. With respect to the discrepancies between negative histopathological findings from forceps biopsy and ER specimens, the frequency of NPD after ER is reported to be 3.2% to 4.4% in previous studies [8,19,20], which is comparable to the 2.5% of cases in our study. They also found that the most common initial pretreatment biopsy diagnosis was LGD, which is in agreement with our data showing a higher prevalence of LGD.…”
Section: Discussionsupporting
confidence: 80%
“…Therefore, ER could be regarded as an improved diagnostic procedure for early gastric neoplasms [5]. With respect to the discrepancies between negative histopathological findings from forceps biopsy and ER specimens, the frequency of NPD after ER is reported to be 3.2% to 4.4% in previous studies [8,19,20], which is comparable to the 2.5% of cases in our study. They also found that the most common initial pretreatment biopsy diagnosis was LGD, which is in agreement with our data showing a higher prevalence of LGD.…”
Section: Discussionsupporting
confidence: 80%
“…Kim et al [34] reported that there was no residual tumor in 3.2 % (20/633) of endoscopically resected gastric dysplasia or EGC. No residual tumor after ESD can be due to complete removal of the lesion at biopsy, pathology overestimation, and incorrect localization [35]. In the present study, there were six cases of no residual tumor in the resected specimen.…”
Section: Discussionmentioning
confidence: 45%
“…Although the detection of simultaneous gastric neoplasms before endoscopic resection enables the treatment of all the lesions at a single time, the cost and benefit of such treatment is uncertain. The cost and risk of repeat endoscopy with biopsy may outweigh the potential benefits of additional information about the primary lesion, which only rarely modifies the treatment strategy [19]. In addition, not only incorrect endoscopic resection but also the presence of simultaneous lesions contribute to the increase in cost.…”
Section: Discussionmentioning
confidence: 99%